2013
DOI: 10.1002/jmri.24396
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging thermometry in multiple sclerosis

Abstract: Brain temperature was significantly lower in MS patients than in healthy controls, probably representing decreased brain metabolism in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The most important roles of magnetic resonance imaging (MRI) in demyelinating diseases include: (i) diagnosis; [1][2][3][4][5] (ii) imaging biomarkers; [5][6][7][8][9][10][11][12][13][14][15][16][17] and (iii) monitoring of sideeffects from disease-modifying drugs. The most important roles of magnetic resonance imaging (MRI) in demyelinating diseases include: (i) diagnosis; [1][2][3][4][5] (ii) imaging biomarkers; [5][6][7][8][9][10][11][12][13][14][15][16][17] and (iii) monitoring of sideeffects from disease-modifying drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The most important roles of magnetic resonance imaging (MRI) in demyelinating diseases include: (i) diagnosis; [1][2][3][4][5] (ii) imaging biomarkers; [5][6][7][8][9][10][11][12][13][14][15][16][17] and (iii) monitoring of sideeffects from disease-modifying drugs. The most important roles of magnetic resonance imaging (MRI) in demyelinating diseases include: (i) diagnosis; [1][2][3][4][5] (ii) imaging biomarkers; [5][6][7][8][9][10][11][12][13][14][15][16][17] and (iii) monitoring of sideeffects from disease-modifying drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The data were also analyzed as a function of age, DD, and LL to provide potential predictors of physical disability in MS patients as measured by EDSS. The LV CSF diffusivity method used in this work has been validated [13, 29, 30] and used previously by others [9, 14, 16] to infer core brain temperature. Water molecular diffusion, relaxation time, and proton frequency shift dependence on temperature is well-documented [31-36].…”
Section: Discussionmentioning
confidence: 99%
“…In patient populations, Yamada and colleagues [9] used this measure to infer that brain temperature is elevated in Moyamoya patients [9]. More recently, Sai and colleagues [16] used this measure on thirteen healthy controls and thirteen MS patients and reported that brain temperature is reduced in MS patients, apparently contradicting a short report of elevated temperature in MS using magnetic resonance spectroscopy [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Sakai et al applied apparent diffusion coefficient (ADC) based thermometry successfully in 45 healthy adults, obtained reliable results, and showed physiological decline in ventricular temperature with increasing age . Using ADC‐based thermometry, the same group showed a reduction in brain core temperature in adults with mild traumatic brain injury and multiple sclerosis and increase in ventricular temperature in adults with moyamoya disease . Changes in brain temperature are most likely caused by a global decrease in brain metabolism in mild traumatic brain injury and multiple sclerosis and a mismatch between cerebral metabolism and perfusion in moyamoya disease .…”
Section: Introductionmentioning
confidence: 99%